Our Best Blue-Ribbon Recipes : A winning collection of top-notch, delicious recipes - Gooseberry Patch (Essex, Connecticut : Gooseberry Patch, 2022)
"Bring family & friends to the table in a jiffy when you serve them blue-ribbon, family-favorite and one-of-a-kind recipes. Filled with our best award-winning and crowd-pleasing recipes, this book showcases the very best recipes from home cooks far and wide. Inside you'll find: mouthwatering recipes for breakfast, lunch & dinner; best-ever appetizers & snacks for amazing quick nibbles; delicious sweet treats you'll be proud to call your own; foolproof handy tips to help every cook in the kitchen."--
Includes index.
"202 delicious medal-worthy recipes"--Cover.
Keywords: Cookbooks; Recipes; Cookbooks